National treatment practices in the management of infectious intracranial aneurysms and infective endocarditis. (4th June 2015) - Singla, Amit; Fargen, Kyle; Blackburn, Spiros; Neal, Dan; Martin, Tomas D.; Hess, Phillip J; Beaver, Thomas M; Klodell, Charles T; Hoh, Brian
Abstract : Introduction: There is an absence of widely accepted guidelines for the management of infectious intracranial aneurysms (IIAs) owing to a dearth of high-quality evidence in the literature. Objective: To better define the incidence of IIAs, treatment practices, and patient outcomes by performing a Nationwide Inpatient Sample (NIS) database query. Methods: We queried the NIS database from 2002 to 2011 for all patients with the primary diagnosis of infectious endocarditis (IE), subarachnoid hemorrhage (SAH), or unruptured cerebral aneurysm by ICD-9-CM codes. ICD-9 procedure codes were used to identify patients undergoing neurosurgical or cardiothoracic procedures. Results: The query identified 393 patients with primary diagnosis of IE, SAH or unruptured cerebral aneurysm treated during 2002–2011. The mean age of the patients was 53.5 years; 244 (62%) were male. The majority of patients presented with SAH (361; 91.9%). Only 73 (18.6%) patients underwent neurosurgical coiling or clipping for IIA. Of patients undergoing a neurosurgical procedure, 65 had SAH (constituting only 18% of patients with SAH) and 8 had unruptured aneurysms (constituting only 25% patients with unruptured aneurysms). Cardiac procedures were performed in only 72/393 patients (18.3%) patients. Only 67 (18.6%) of the patients with SAH and 5 (15.6%) with unruptured aneurysms underwent a cardiac corrective surgical procedure. Mortality was significantly higher in those patients managed conservatively (26.7%) than in those who underwent clipping or embolization (15.1%; p<0.001). Conclusions: In this NIS database study, the majority of patients with IIAs were managed non-operatively, regardless of rupture status. Further investigation is warranted to standardize the management of these lesions.